PENERAPAN OTONOMI DAERAH DALAM DESENTRALISASI KORUPSI DI DAERAH - Kholik, Saeful (Universitas Wiralodra, 2017)
The Article 18 of 1945 Constitution explains about the governance system in Indonesia recognizes the existence of central government and local government. The formation of local governance is based on the conditions of the vast territory of the country. Broad regional autonomy has the elaboration of decentralization in its entirety ideally the implementation in broad regional autonomy must have a principle of Democracy, Justice, Equity, Empowerment and Community Participation focused on increasing Economy in the region Each with the principle of Decentralization, but the implication of this declaration also makes the corruptors in the area more freely covered in a public policy or Public Policy is covered in an idea and the realization of activities in the area.